Carbohydrate composition, viscosity, solubility, and sensory acceptance of sweetpotato- and maise-based complementary foods - Amagloh FK; Mutukumira AN; Brough L; Weber JL; Hardacre A; Coad J (Food and Nutrition Research, 2013)
Background: Cereal-based complementary foods from non-malted ingredients form a relatively high viscous porridge. Therefore, excessive dilution, usually with water, is required to reduce the viscosity to be appropriate for infant feeding. The dilution invariably leads to energy and nutrient thinning, that is, the reduction of energy and nutrient densities. Carbohydrate is the major constituent of food that significantly influences viscosity when heated in water. Objectives: To compare the sweetpotato-based complementary foods (extrusion-cooked ComFa, roller-dried ComFa, and oven-toasted ComFa) and enriched Weanimix (maize-based formulation) regarding their 1) carbohydrate composition, 2) viscosity and water solubility index (WSI), and 3) sensory acceptance evaluated by sub-Sahara African women as model caregivers. Methods: The level of simple sugars/carbohydrates was analysed by spectrophotometry, total dietary fibre by enzymatic-gravimetric method, and total carbohydrate and starch levels estimated by calculation. A Rapid ViscoTM Analyser was used to measure viscosity. WSI was determined gravimetrically. A consumer sensory evaluation was used to evaluate the product acceptance of the roller-dried ComFa, oven-toasted ComFa, and enriched Weanimix. Results: The sweetpotato-based complementary foods were, on average, significantly higher in maltose, sucrose, free glucose and fructose, and total dietary fibre, but they were markedly lower in starch content compared with the levels in the enriched Weanimix. Consequently, the sweetpotato-based complementary foods had relatively low apparent viscosity, and high WSI, than that of enriched Weanimix. The scores of sensory liking given by the caregivers were highest for the roller-dried ComFa, followed by the oven-toasted ComFa, and, finally, the enriched Weanimix. Conclusion: The sweetpotato-based formulations have significant advantages as complementary food due to the high level of endogenous sugars and low starch content that reduce the viscosity, increase the solubility, impart desirable sensory characteristics, and potentially avoid excessive energy and nutrient thinning.
Keywords: Science & Technology; Life Sciences & Biomedicine; Food Science & Technology; Nutrition & Dietetics; carbohydrate; complementary/infant food; sensory; simple sugars; sweetpotato; viscosity; DEVELOPING-COUNTRIES; ENERGY DENSITY; ALPHA-AMYLASE; INFANT FOOD; SUGAR; PORRIDGES; EXTRUDATE; QUALITY; GRUELS; STARCH; 0908 Food Sciences; 1111 Nutrition and Dietetics